Meta-romantika kot paradigma sodobne slovenske drame - Kozak, Krištof Jacek (Slavistična revija, 2006)
After postmodernism the contemporary Slovenian drama has been turning towards traditionian, but taking it into consideration in a new and fresh manner. On the one hand it has returned to dramatic genres and on the other it again understands the protagonists as uniform subjects. Z. Hočevar's 'M te ubu! I will kill ya! serves as the paradigm for the analysis, as it includes innovatios both in terms of form and content, which are then combined. New artistic endeavours hold a mirror to contemporary man, in which s/he can see his/her whole image. On the basis of this, the term metha-romanticism has been suggested to desciribe the new direction of Slovenian drama.
Keywords: Hočevar, Zoran; literarne zvrsti; meta romantika; slovenska dramatika; slovenska književnost; subjekt